2006
DOI: 10.1111/j.1471-0528.2005.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length in small‐for‐gestational‐age babies

Abstract: Objective Short telomeres are associated with adult cardiovascular disease. Our aim was to determine whether small-for-gestationalage (SGA) newborns have shortened telomeres compared with appropriately grown controls.Design Prospective cohort study.Setting Large tertiary referral unit in Trent, UK.Population Seventy-two women who delivered at 35-42 weeks of gestation were recruited; 34 delivered SGA babies (less than or equal to the third birthweight centile) and 38 had appropriately grown babies (greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 21 publications
11
88
4
1
Order By: Relevance
“…This relationship between low birth weight and shorter TL has been found previously in placenta samples (Davy et al, 2009) but was not found in a small study measuring TL in cord blood (Akkad et al, 2006) nor in three cohorts (including 124 MZ and DZ twin pairs) from Finland (Kajantie et al, 2012). These negative reports do not necessarily contradict our findings.…”
Section: Discussionsupporting
confidence: 70%
“…This relationship between low birth weight and shorter TL has been found previously in placenta samples (Davy et al, 2009) but was not found in a small study measuring TL in cord blood (Akkad et al, 2006) nor in three cohorts (including 124 MZ and DZ twin pairs) from Finland (Kajantie et al, 2012). These negative reports do not necessarily contradict our findings.…”
Section: Discussionsupporting
confidence: 70%
“…Premature senescence in the kidney may result from ongoing hyperfiltration injury in kidneys with fewer nephrons, compounded by a rapid increase in body size. In humans, leukocyte telomere length was not different between LBW and NBW British newborns, but among 5 year old children from Bangladesh, telomeres were significantly shorter in those who were of LBW 93,94 . Senescence is linked to oxidative stress.…”
Section: Early Growth and Kidney Functionmentioning
confidence: 77%
“…In such a situation, availability of a pool of cells for maintenance or for postinjury renal cellular turnover would be limited in kidneys that have already exhausted telomere capacity during a past period of catch-up growth (Figure 2). Although we would not expect significantly shorter telomeres in LBW infants, as has been reported (65), it would be of interest to follow telomere length longitudinally in LBW infants who have experienced catch-up growth in comparison with control counterparts. We would expect reduced telomere length (and hence limited subsequent replicative capacity) after a period of catch-up growth.…”
Section: Role Of Telomere Integrity and Renal Cell Turnovermentioning
confidence: 99%